A General Overview of Context-Based Learning Studies in Secondary Science Teaching In Turkey - Cınıcı, Ayhan (Research Trends In Educational Sciences, 2025)
Context Based Learning (CBL) is an approach that aims to raise science literate individuals who know how to use this knowledge in the relevant context by associating scientific knowledge with the events and problems that can be encountered in daily life and thus builds a bridge betweendaily life events and course material. The number of studies related to CBL is increasing day by day. At this point, the aim of this study is to make a thematic content analysis of the research articles on the CBL approach in secondary science education carried out in Turkey. In the study, the research articles were analyzed and evaluated in terms of purpose, methodology (research model, sampling, data collection tools, analysis methods), main findings, conclusions and recommendations. The aim of the study is to present a holistic perspective to guide new studies by revealing the trends and gaps in the related literature. The results showed that the studies focusing on determining the effects of context-based instruction on students’ achievement, conceptual/contextual understanding, association and transfer levels are quite common in literature. In this respect, it is thought that there is a need for future studies to investigate the effects of context-based teaching on skills and thinking processes.